2023
DOI: 10.3390/biomedicines11020459
|View full text |Cite
|
Sign up to set email alerts
|

Development of a TGFβ—IL-2/15 Switch Receptor for Use in Adoptive Cell Therapy

Abstract: Therapy employing T cells modified with chimeric antigen receptors (CARs) is effective in hematological malignancies but not yet in solid cancers. CAR T cell activity in solid tumors is limited by immunosuppressive factors, including transforming growth factor β (TGFβ). Here, we describe the development of a switch receptor (SwR), in which the extracellular domains of the TGFβ receptor are fused to the intracellular domains from the IL-2/15 receptor. We evaluated the SwR in tandem with two variants of a CAR th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The CD19 CAR is identical to JK11, except for the scFv, and resembles the construct used in tisagenlecleucel (fmc63scFv_CD8aTM/spacer_41BB-z), which is approved for use against leukemia [ 1 ]. The T cells were co-cultured overnight with tumor target cells using a panel of STEAP1-positive (22Rv1, C2-4B, LNCap) and STEAP1-negative (22Rv1 STEAP1 knockout) prostate cancer cells that we have previously described [ 13 , 36 ]. The production of IFNγ and TNFα was measured by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…The CD19 CAR is identical to JK11, except for the scFv, and resembles the construct used in tisagenlecleucel (fmc63scFv_CD8aTM/spacer_41BB-z), which is approved for use against leukemia [ 1 ]. The T cells were co-cultured overnight with tumor target cells using a panel of STEAP1-positive (22Rv1, C2-4B, LNCap) and STEAP1-negative (22Rv1 STEAP1 knockout) prostate cancer cells that we have previously described [ 13 , 36 ]. The production of IFNγ and TNFα was measured by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…CAR T cells armored with factors that can reduce chemo-repulsion may be able to overcome the functional or dynamic barriers that exclude them from tumor nests [ 20 ]. Examples include dominant negative [ 58 ] or switch TGF-β receptors that make CAR T cells resistant to the immune repulsive and suppressive effects of TGF-β [ 47 , 59 , 60 ]. Moreover, epigenetic knockdown of PD1 expression in response to Ag encounter can overcome dynamic barriers dependent upon PD1/programmed death ligand 1 at the periphery of tumor nests [ 20 , 61 ].…”
Section: Direct (Primary) Versus Indirect (Secondary) Cancer Cell Kil...mentioning
confidence: 99%
“…21 Given its dual role in both promoting tumor growth and suppressing immune cells, multiple strategies are currently being explored to mitigate the effects of TGF-β. These include targeting the latency-associated peptide, 22 leveraging the αv integrin/TGF-β axis, 23 inhibiting the TGF-β 24 or kinase receptor type I using small molecule inhibitors, 25 employing TGF-β switch receptor, [26][27][28] and TGF-β CAR T cells. 29 However, these methodologies also raise considerable safety issues, as it has been confirmed that first-generation TGF-βRI inhibitors can result in cardiac toxicity.…”
Section: Introductionmentioning
confidence: 99%